Field Performance of Eight Commercial Date Palm Cultivars of Balochistan Grown under Agro-Climatic Conditions of District Khairpur, Pakistan - Solangi, Najamuddin; Soomro, Nazir Ahmed; Jatoi, Mushtaque Ahmed; Ghulam Sarwar Channa; Mirani, Abdul Aziz; Abul-Soad, Adel Ahmed; Markhand, Ghulam Sarwar (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Field performance of eight commercial date palm cultivars of Balochistan was carried out under agro-climatic conditions of district Khairpur, Pakistan. Five years old offshoots of different date palm cultivars brought from Turbat and Panjgoor, Balochistan, and were cultivated in the Research Orchard of Date Palm Research Institute, Shah Abdul Latif University, Khairpur. In this study, vegetative, flowering, bunch and fruit physical characteristics were studied after ten years of plantation in the field. Fruits of different cultivars were collected at three distinct fruit growth stages (kimri, khalal and rutab) for morphological characterization (fruit colour, fruit length, fruit diameter, fruit weight, seed length, seed diameter, seed weight). Results of vegetative characteristics revealed that higher leaf/frond length (187.3 cm), pinnae number (208.6) and spine number (26.6) was observed in cv. Begum Jangi. Flowering characteristics showed that highest number of spathes (14.3) and number of strings per spathe (88.6) were noted in cv. Begum Jangi. Highest bunch length (44.6 cm) and bunch weight (15.4 kg) was observed in cv. Muzawati. Highest fruit length (4.3 cm, 5.3 cm and 5.6 cm) was recorded in cv. Aab-e-dandan at kimri, khalal and rutab stages respectively. Highest fruit weight (22.5 g) was observed in cv. Muzawati at kimri stage, 23.3 g in cv. Shakri at khalal stage and 24.0 g in cv. Muzawati at rutab stage. Highest seed length (2.41 cm) was noted in cv. Gogna at kimri stage, 2.97 cm at khalal and 3.0 cm at rutab stages were observed in cv. Aab-e-dandan. Higher pulp/fruit ratio (PFR) (94.6%) was observed in cv. Muzawati at khalal stage, whereas at rutab stage higher pulp/fruit ratio (94.4%) was recorded in cv. Halini at edible rutab stage. Findings of the current study revealed that soil and climate of district Khairpur were suitable for the cultivation of exotic commercial date palm cultivars in the area.